Kebahagiaan pada Bhikkhu Theravada - Mutia Avezahra; Fattah Hanurawan; Ninik Setiyowati (Flourishing Journal, 2021)
The essence of Buddhism teaching is endowed from the core ideas of Siddhartha Gautama, or who was then called as Shakyamuni Buddha. Buddhist’s life guide is set in sila, in which it is in accordance with the group (Buddhist Parisad). In actual practice, the Theravada Bhikkhu leave their family life to have a simple life, they should not eat after the noon, they are not allowed to listen to a song, watch dance performance, not allowed to do anything that aims to fulfill sense happiness. By observing Bhikkhu’s life that is full of limitations, the researcher interested to study the happiness in Theravada Bhikkhu. The research aims at revealing the happiness in Theravada Bhikkhu in Indonesia. Qualitative is chosen as the method, with phenomenological approach model. The research subject includes three Theravada Bhikkhu in Padepokan Dhammadipa Arama Batu East Java, Indonesia. The data collected by in-depth interviews, field notes, and gathered from documents. The data were analyzed using thematic analysis and validated using participant checks. The results showed that the meaning of happiness for Theravada Bhikkhu is the creation of clean mental state; a condition in which the mind is free from things that shackle the self. In this study, happiness in Theravada Bhikkhu is reflected in three aspects: cognitive, positive relationships with others, and personality. Hakikat ajaran Budha dapat diketemukan melalui pemikiran inti dari pemikiran Sidharta Gautama atau kemudian disebut Shakyamuni Budha. Panduan kehidupan umat Budha diatur dalam sila sesuai dengan kelompok umat Budha (Budha Parisad). Di dalam praktik yang nyata, para Bhikkhu Theravada meninggalkan kehidupan berkeluarga, menjalani kehidupan sederhana, tidak boleh makan lebih dari jam 12 siang, tidak diperbolehkan mendengarkan lagu, melihat tari-tarian dan tidak melakukan sesuatu yang bertujuan kesenangan indria semata. Melihat tata cara kehidupan Bhikkhu yang penuh batasan itulah, penulis tertarik untuk meneliti tentang kebahagiaan pada Bhikkhu Theravada. Tujuan penelitian ini adalah mengungkapkan kebahagiaan pada Bhikkhu Theravada di Indonesia. Metode dalam penelitian ini adalah penelitian kualitatif dengan model pendekatan fenomenologi. Subjek pada penelitian ini adalah tiga Bhikkhu Theravada di Padepokan Dhammadipa Arama Batu Jawa Timur Indonesia. Pengumpulan data dilakukan dengan wawancara mendalam (in depth interview), catatan lapangan (field notes) dan dokumen. Teknik analisis data menggunakan analisis tematik dan validasi data menggunakan cek partisipan. Hasil penelitian menunjukkan bahwa makna kebahagiaan pada Bhikkhu Theravada adalah terciptanya kondisi batin yang bersih, artinya sebuah kondisi di mana batin terbebas dari hal-hal yang dapat membelenggu diri. Kebahagiaan pada Bhikkhu Theravada pada penelitian ini tergambar pada tiga aspek kebahagiaan yakni aspek kognitif, aspek hubungan positif dengan orang lain dan aspek kepribadian.